1980
DOI: 10.1007/bf02407183
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 1α-hydroxyvitamin D3 and 24R,25-dihydroxyvitamin D3 on bone remodeling

Abstract: The present study was undertaken to evaluate the effects of 1 alpha-hydroxyvitamin D3 and 24R,25-dihydroxyvitamin D3 on bone remodeling in dogs with osteomalacia induced by vitamin D depletion. To assess the rates of skeletal remodeling, intravital tetracycline labeling and morphometry of surface pattern were employed. Either vitamin D3 derivative accelerated the appositional growth rate, increased the percentage of osteoid seams labeled, and decreased the number, width, and perimeter of new osteoid seams. But… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…Thus, 24,25(OH)2D3 enhanced the mineralization of previously formed osteoid in the absence of any quantitative effect on the rates of either bone or matrix formation. These findings agree with those of Galus et al [17] who found a reduction in the width of osteoid seams in osteomalacic dogs given 24,25(OH)zD 3. The present results differ, however, in that increments in the rate of bone apposition, as reported by these investigators, were not observed.…”
Section: 25(oh)2d 3 Is the Most Active Metabolite Of Vitamin D On Asupporting
confidence: 94%
“…Thus, 24,25(OH)2D3 enhanced the mineralization of previously formed osteoid in the absence of any quantitative effect on the rates of either bone or matrix formation. These findings agree with those of Galus et al [17] who found a reduction in the width of osteoid seams in osteomalacic dogs given 24,25(OH)zD 3. The present results differ, however, in that increments in the rate of bone apposition, as reported by these investigators, were not observed.…”
Section: 25(oh)2d 3 Is the Most Active Metabolite Of Vitamin D On Asupporting
confidence: 94%
“…In this context it should be mentioned that when 24,25(OH)2D3 was administered to rachitic dogs the number of resorption cavities and the length of resorption sites was reduced to normal concomitantly with an increase in the rate of oppositional growth of bone [Ornoy et al, 1978;Gallus et al, 1980]. Our results further corroborate different previous studies [Dekel et al, 1979;Edelstein and Ornoy, 1979], pointing towards a major role of 24,25(OH)2D3 in bone metabolism.…”
Section: Discussionsupporting
confidence: 82%
“…There is a growing body of evidence that both 1,25-(OH) 2 D and 24,25-(0H) 2 D are required for optimal vitamin D action on bone formation, mineralization, and remodelling (3,5,(52)(53)(54). In vitamin D-depleted dogs with osteomalacia, the administration of either metabolite increased the rate of appositional bone growth.…”
Section: Discussionmentioning
confidence: 97%